Impact of Child Selected Customization of Twin Block Appliances on Acceptance and Compliance: A Pilot Randomized Clinical Trial - Ahmed Akram EL-Awady, Khaled Farouk Abdallah; Abdelhamid Abuelyazid Abdelhamid Eissa; Mohamed Mohamed Ali, Marwa Hassan Abdelmoniem; Ahmed Talaat Hussein Ali, Abdallah Mohammed Bahaa El-Din; Salam Mohamed EL Araby, Sara Elkabbany; Tamer Abdellatif Elmansy (Journal of Carcinogenesis, 2026)
Background: Treatment acceptance and compliance are critical determinants of successful Twin Block therapy. Child-centered customization of removable appliances may enhance treatment engagement; however, evidence regarding its influence on acceptance and compliance remains limited. Aim: To evaluate the effect of child-selected customization of Twin Block appliances on treatment acceptance and self-reported compliance among children with Class II malocclusion. Methods: This multicenter, two-arm, parallel pilot randomized clinical trial included 30 children aged 8–12 years presenting with Class II malocclusion requiring Twin Block therapy. Participants were randomly allocated to receive either a conventional Twin Block (n = 15) or a customized Twin Block incorporating child-selected aesthetic features (n = 15). Treatment acceptance was assessed using a validated child-reported questionnaire, while self-reported compliance was evaluated using a single-item Likert scale. Assessments were performed at 1 week, 3 months, and 6 months after appliance delivery. Results: Children in the customized group demonstrated significantly higher acceptance scores than those in the conventional group at all follow-up periods (p < 0.001). Acceptance scores gradually decreased over time in both groups; however, the customized group maintained significantly higher acceptance throughout the study period. Self-reported compliance was significantly higher in the customized group at 1 week (p = 0.006), but no significant differences were observed at 3 months (p = 0.185) or 6 months. Conclusions: Child-selected customization of Twin Block appliances significantly improved treatment acceptance and enhanced short-term compliance. Although the effect on compliance diminished over time, customized appliances consistently achieved higher acceptance scores than conventional appliances. Incorporating child-centered customization strategies may improve children’s experiences during removable functional orthodontic treatment.